Answer:
![\Longrightarrow: \boxed{\sf{-2a-12}}](https://img.qammunity.org/2023/formulas/mathematics/high-school/x0s1pugd670ht9tl5wfe3d40aac5ravl2t.png)
Explanation:
Use the distributive property.
![\underline{\text{DISTRIBUTIVE PROPERTY:}}\\\\\Longrightarrow: \sf{A(B+C)=AB+AC}](https://img.qammunity.org/2023/formulas/mathematics/high-school/1zh4j9nhlxo4w2a1nv79zig15lgj0jh4a3.png)
6a-4(2a+3)
First, multiply by expand.
⇒ -4(2a+3)
⇒ -4*2a=-8a
⇒ -4*3=-12
⇒ -8a-12
→ 6a-8a-12
Solve.
Add or subtract the numbers from left to right.
⇒ 6a-8a=-2a
= -2a-12
![\Longrightarrow: \boxed{\sf{-2a-12}}](https://img.qammunity.org/2023/formulas/mathematics/high-school/x0s1pugd670ht9tl5wfe3d40aac5ravl2t.png)
- Therefore, the correct answer is -2a-12.
I hope this helps! Let me know if you have any questions.